Prophets and Politics in Zimbabwe - Manyeruke, Charity; Hamauswa, Shakespear (Prophets, Profits, and the Bible in Zimbabwe: Festschrift for Aynos Masotcha Moyo, 2013)
In Zimbabwe, as is the case in almost all states, politics and religion are inextricably twined together. The role of the spirit mediums and the church throughout the pre-colonial and during the colonial era attest to this. This chapter unpacks the interface between prophets and politics in Zimbabwe. Prior to the 21st century, garment prophets were largely predominant in the country. The Johane Marange and Madzibaba Wimbo are cases in point. The current wave, which started around 2007, has seen the coming in on board of Pentecostal young male prophets such as Emmanuel Makandiwa, Uebert Angel, and Wutabwashe. International prophetic figures such as TB Joshua and Pastor Chris are also influencing Zimbabwean politics. Some of their prophecies have since sent shivers into the spines of politicians who are reacting mostly with anger. Unfortunately, such negative reactions are not in tandem with unprecedented increase in the participation of politicians at various church gatherings. In turn, prophets such as Makandiwa have participated at national gatherings such as the anti-sanctions campaign, leaving many questions regarding the relationship between politics and prophets in Zimbabwe. The study employs a longitudinal research design to examine the changing relationship between prophets and politics since 2000. However, to provide a foundation for the understanding of the current developments, the study provides a short survey of what has been happening in Zimbabwe before colonialism as well as during the colonial period. Documentary search was used to gather data from published documents such as newspapers, church documents, journal articles, books and internet sources.
free